Tn125-Related Acquisition of bla(NDM)-Like Genes in Acinetobacter baumannii - Poirel, Laurent (American Society for Microbiology, 2012)
A multidrug-resistant Acinetobacter baumannii isolate recovered from a patient hospitalized in Switzerland after a transfer from Serbia produced the NDM-1 carbapenemase. The bla(NDM-1) gene was part of a chromosomally located Tn125 composite transposon bracketed by two copies of the same insertion sequence, ISAba125. This transposon was also associated with the acquisition and expression of the bla(NDM-2) gene in an A. baumannii isolate in Germany. Tn125 appears to be the main vehicle for dissemination of bla(NDM) genes in that species.